Vertical Carbon Export in a Changing Arctic Seasonal Ice Zone: Composition and seasonality in the area north of Svalbard and in an Arctic glacial fjord - Dybwad, Christine (UiT The Arctic University of Norway, 2023)
The ocean’s biological carbon pump (BCP) is a vital part of the global carbon cycle as it produces, transforms, and transfers organic carbon from the surface ocean to the deep. To model the oceans capacity to store carbon today and in the future, we need to understand these processes well. In the Eurasian Arctic, the marine ecosystems who control most of the BCP face a rapid decline in sea ice cover, ocean warming and the increased prominence of the Atlantic water (AW), as well as glacier mass loss in their fjords. The aim of this work was to investigate the current seasonal patterns and to identify the relative protist, zooplankton fecal pellet and detritus composition of vertical carbon export in the northward-retreating and AW influenced seasonal sea ice zone north of Svalbard and in an Arctic glacial fjord (Billefjorden, Svalbard), using short- and long-term sediment traps. The key findings of this thesis include, 1) clear and comparable seasonal patterns in vertical carbon export across study sites and sediment trap designs, 2) diatom blooms and zooplankton fecal pellets were important constituents of heightened vertical carbon fluxes, especially where AW advected blooms into unfavorable light conditions or brought in high abundances of zooplankton, and 3) estuarine circulation and high turnover of nutrients and production drive vertical carbon export in a fjord experiencing glacier transition. Our studies suggest than in an Arctic where seasonal ice is reduced, the annual amount of organic carbon exported to depth may not change but that it will be increasingly reworked rather than phytoplankton derived. This thesis provides the first measured annual vertical carbon export rates in the region north of Svalbard and highlights the role of AW and plankton communities in driving the BCP in these highly dynamic and rapidly changing regions of the Arctic. Koblingen av planteproduksjon i de lysrike overflatelagene i havet og havdypet der mange organismer lever påvirkes av klimaendringer. I det arktiske marine ...